Towards a greater integration of environmental sustainability into product innovation: action research and proposition of an ecodesign transition framework - Bronès, Fabien Albert (2015)
Since the 1990s, the evolution to more environmentally sustainable business operations has gained increased recognition incorporations and the Academia, with sustainability becoming a key competitive priority for companies. In spite of a large amount of research on ecodesign,or the integration of environmental aspects into product design and development, recent surveys state that thorough ecodesign implementation is still a challenge for most firms.To overcome gaps found in prior studies (such as a distance between theory and practice, and over-technical and fragmented recommendations), this research aimed to identify and experiment how to incorporate environmental sustainability more effectively into product innovation and related activities of a company, and to propose a framework summarising the associated learning. This thesis is based on a set of five articles, applying a multi-methods approach. The framework was built with a methodology combining systematic reviews of previous literature and action research through a five-year long experiment. Inside a leading Brazilian cosmetics company, two implementation cycles were conducted, including customisation of ecodesign tools and their application in eight product development projects, and wide capacity building involving different stakeholders. The research led to three contributions. As a first methodological contribution, action research methodology and application guidelines were developed, for an effective collaboration mode between the Academia and companies, especially adapted to sustainable open innovation. Secondly, this study has deepened and experimented in real company context a broad view of ecodesign related activities, expanding the recognised approach centred on individual projects and validating the concept of formal insertion of customised ecodesign tools into of the Product Development Process. Such principle was further extended to include other managerial aspects, such as project and portfolio management, and linking them with strategic planning. To complement such technical and process related aspects, new \"soft\" side approaches were also experienced, building on the Transition Management theory. The third and major contribution, deriving from a synthesis of more than fifty models found in the literature and the action research, is the proposition of an \"Ecodesign Transition Framework\". The so-called \"15Ps ETF\"comprehends a \"pattern\" with eight main constructs (Purpose, Portfolio, Process, Platform, Pipeline, Practices & tools, Procedures and Project management) for a mature ecodesign and a \"pathway\" component, with five constructs (Planet, Public, Programme, Pilot, and People), for conducting the necessary transition addressing soft issues. The central \"Aztec pyramid\" shape of the framework represents the systemic three-level structure, combining the strategic, tactical and operational product related processes and activities. The ETF intends to support a far-reaching approach to better plan, implement and monitor the integration of environmental considerations in the whole innovation process of a company, through a systemic action learning process. The overall increased ecodesign maturity observed in the company showed congruence with the framework, with substantial challenges also observed. For further validation, the ETF could be applied in different contexts, and explored through qualitative and quantitative studies of associated limiting or success factors, to better address corporate specificities and complexity (e.g., culture, resistance to change, organisational entropy, etc.).